Temperature tolerance and survival of intertidal populations of the seagrass Zostera noltii (Hornemann) in Southern Europe (Ria Formosa, Portugal) - Massa, S. I. (2014)
The dwarf seagrass Zostera noltii is an important primary producer in Atlantic coastal ecosystems from Mauritania to southern Norway and the Mediterranean Sea. Sessile intertidal organisms existing at the interface between marine and terrestrial environments may be particularly vulnerable to environmental change. In this study, we asked how near to thermal tolerance limits natural populations of Z. noltii are in the Ria Formosa coastal lagoon system in southern Portugal. We recorded the maximum temperatures in the Ria Formosa during the 2007 summer, and conducted experiments to determine the sub-lethal temperature of Z. noltii shoots sampled at two sites located at different tidal heights. Mortality rates and photosynthetic performance were recorded within a range of heat shock temperatures between 35 and 41 C. Survival was recorded B37 C, while higher temperatures led to a sudden drop in photosynthetic capacity followed by mortality (shoot loss) that occurred more rapidly with increasing temperatures. At 39 C and above, the rate of shoot mortality in both sites was close to 100%, occurring between 5 and 13 days after the heat shock. Survival was ca. 95 and 90% at 35 and 37 C, respectively. From these results for Z. noltii populations in the Ria Formosa we estimated sub-lethal temperature to be approximately 38 C for Z. noltii, close to the maximum of 36 C recorded in the summer 2007. Considering predicted trajectories in the coming decades, these results raise concern as to the future viability of intertidal Z. noltii populations near the southernmost edge of their distribution.